Konsep social cognitive career theory - Nilma Zola; A. Muri Yusuf; Firman Firman (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
Social Cognitive Career Theory (SCCT) is a career development model that describes how individual inputs, contextual affordances, and sociocognitive variables influence the establishment of occupational interests, career objectives, and behaviors. SCCT emphasizes the relevance of learning experiences, self-efficacy, and outcome expectations in the career development process, and is based on Bandura's social cognitive theory. SCCT is also interested in the relationships between sociocognitive characteristics, professional interests, and other career outcomes, as well as race/ethnicity, gender, and predispositions. Existing research generally supports specific SCCT approaches; nevertheless, a study of the literature found significant SCCT research limitations. The goal is for counselors to have a better grasp of the complicated mechanisms through which people establish career interests.